Odpowiedź :
Odpowiedź:
Zad 1
a) 5x = 120 /:5
x = 24
spr:
5 * 24 = 120
b) 4x + 6 = 38
4x = 38 - 6
4x = 32
x = 8
spr:
4 * 8 + 6 = 38
32 + 6 = 38
c) 6x - 11 = 25
6x = 25 + 11
6x = 36
x = 6
spr:
6 * 6 - 11 = 25
Zad 2
5x - 7 - x = 9 - 2x - 4
5x - x + 2x = 9 - 4 + 7
6x = 12
x = 2
spr:
5 * 2 - 7 - 2 = 9 - 2 * 2 - 4
10 - 7 - 2 = 9 - 4 - 4
1 = 1
Odpowiedź:
5 * x = 120
x = 120 : 5
x = 24
spr 5 * 24 = 120
4 * x + 6 = 38
4 * x = 32/:4
x = 8
spr 4 * 8 + 6 = 38
6 * x - 11 = 25
6 * x = 36/:6
x = 6
spr 6 * 6 - 11 = 25
5 * x - 7 - x = 9 - 2 * x - 4
5x - 7 - x = 9 - 2x - 4
5x - x + 2x = 9 - 4 + 7
6x = 12
x = 12 : 6
x = 2
spr 5 * 2 - 7 - 2 = 9 -2 * 2 - 4
10 - 9 = 9 - 4 - 4
1 = 1